Improving the electrochemical performance of LiNi0.5Co0.2Mn0.3O2 via surface modification with Li1.3Al0.3Ti1.7(PO4)3 coating - Nianchun Yao; Min Zhang; Yulin He; Keyin Cao; Ying Li; Ziqiang Wang (Electrochemistry Communications)
This paper presents a simplified process for synthesizing LiNi0.5Co0.2Mn0.3O2 (NCM523) coated with Li1.3Al0.3Ti1.7(PO4)3 (LATP) to optimize electrochemical characteristics by adjusting LATP content adjustment. LATP, as a superior Li-ion conductive layer, reduces polarization and enhances cycling performance at 50 °C. X-ray diffraction (XRD) confirms that all samples maintain a stable alpha-NaFeO2 layered structure. Performance tests of half and full batteries at room temperature and 50 °C show that the 2 wt% LATP-coated sample exhibits the best electrochemical performance. Cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) show that the LATP-coated sample has higher lithium ion diffusion coefficients and lower charge transfer resistance, which improves rate capability.